Tax regulation on blockchain and cryptocurrency: The implications for open innovation - Andrea Peláez-Repiso; Pablo Sánchez-Nú\~nez; Yolanda García Calvente (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Blockchain is a technology that will change the relationships between the different actors in society, individuals, companies and administration, in aspects as important as taxation, by implementing concepts such as Self-sovereign identity (SSI) and Smart Contracts; which support, for example, virtual currencies, that are not controlled by any state, financial institution or centralized company. Hence, the growing interest of researchers, investors, traders, marketers, enterprises, and administrations to know the scope of this new technology and its tax implications. The main objective of this work is to clarify the status of these studies, explore issues, methods, findings, and trends as well as to define their meaning within the current research scenario. To achieve these objectives, bibliometric analysis was carried out, retrieving 349 research papers, and analyzing 343 papers published between 2015-2019 based on the results of the Web of Science (WoS).
Keywords: 650; bibliometrix; e-commerce; financial law; financial markets; informetrics; legal; science mapping analysis; scientometrics; virtual currencies; virtual money